A STUDY ON THE NATURAL HISTORY OF SPONDYLOLYSIS AND SPONDYLOLYSTHESIS - SAKAGAWA, Hajime (Journal of The Showa Medical Association, 1988)
The patients with spondylolysis or spondylolisthesis in the lumbar region, who had been cared not less than 10 years since they were first diagnosed as such, were studied in order to elucidate the natural history of these diseases. The subjects were 55 in all. The age of the patients ranged from 4 to 75 years old (40.5±15.9 years old on the average) at the time of first diagnosis. The period of time which had paseed since their first diagnosis ranged from 10 to 16 years (11.6±1.5 years on the average) . As a result, JOA score for clinical symptoms was improved from the average score of 24.7±2.3 at the time of first diagnosis to the average score of 27.1±2.8 at the time of this study, though no case was improved in the roentogenography. Only 4 cases (their score at the time of this study were 14, 17, 24, and 25, respectively) were found worse. The improvement in the score for the activitied of daily living contributed to the improving tendency at the time of this study. In conclusion, the conventional conservative therapy should be taken to treat the patients with spondylolysis, and preventive operation is not considered necessary even for the treatment of the patients with complication of spondylolysis and spondylolisthesis.